Evaluation of Major Irrigation Projects - Some Case Studies - Planning Commission (Planning Commission, 1965)
At the instance of the Planning Commission, the Programme Evaluation Organisation undertook a field study of the problems of utilisation of the potential created by some of the new major irrigation projects. the study was initially taken up in nine projects which had been included in the First Five-Year Plan. There were a number of difficulties faced in carrying out this study. In many cases, some of the pertinent data were of a confidential nature and could not be freely used. Besides, there were other difficulties presented by the general state of irrigation statistics. In any case, a note based on some of the field observations was circulated in the Planning Commission. Faced with this situation, it was decided to reorient the objective of this study to include more generally the problems faced in the execution and administration of the projects including the extension of irrigation benefits. It was also considered useful to attempt a benefit cost assessment of these projects. It is with these objectives that some futher observations were initiated in eight of these project areas and an intensive search made for relevant data from various sources.
Programme Evaluation Organisation Planning Commission Government of India